Exploring The Dynamics Between Innovation And Human Development: Evidence From OIC Member Countries - Arifah, Nurul; Siti Aisyah (Jurnal Ekonomi, 2024)
The purpose of this study is to ascertain how the global innovation index, employment, inflation, and urban population all affect human development in a country. A sample of 13 member nations of the Organization of Islamic Cooperation (OIC) were chosen, the timeframe was between 2012 and 2021 using a purposive sample strategy. We utilized a quantitative approach and panel-balanced modeling approaches. The results demonstrate that while inflation has a negative impact on the Human Development Index (HDI), employment and urban development have a favorable impact, and Global Innovation has no effect on HDI. We restricted the sample to low-income and impoverished nations, as they make up the majority of OIC members. Studies on various factors influencing the Human Development Index in members of OIC have yielded mixed results. Consequently, additional study is required to close this knowledge gap and offer a more comprehensive grasp of the variables affecting the Human Development Index in OIC member nations. The findings suggest that governments need to improve access to decent jobs both in urban and rural areas, and most importantly advocate sustainable urban development along with communities and the private sector.